Preliminary Trials on juvenile Macrobrachium rosenbergii Production under modified Static 'Green water' Conditions - Cheah, S. H.; Ang, K. J. (1979)
The methods of juvenile production of Udang Galah (Macrobrachium rosenbergii) have been documented by several workers (ling, 1969 .. Ling and Costello, 1976 .. Fujimura 7966, 1967, 1968, 1972 .. Fujimura and okomoto, 1970,. Sandifer etl.1976). The methods given by these workers involve intensive hatchery management such as frequent water change and cleaning of larval tanks to ensure good sanitation. Such a technique would involve wastage of sea water and at the same time is labour intensive. 'to overcome the above mentioned problems a study 'was conducted at the hatchery of the Faculty of Fisheries and marine Science, Serdang, to produce" Udang Galah" juveniles 'Without water change and by using «green water' at salinities 6~8°100 and 12-14% 0 respectively. Previous studies by Cohen et al. (1976) have conclusively shozon that (green water' is an efficient system to remove toxic metabolites such as ammonia from the culture medium. The 'green water' 'which mainly consists of unicellular algae such as Chlorella is produced by expos;'lg 'loater of salim'ty 6°(00 'Which contained Sarothcrodon mossambicus to sunlight (Fujimura,